Dissecting the Genetic Susceptibility to Graves’ Disease in a Cohort of Patients of Italian Origin - Lombardi, Angela; Menconi, Francesca; Greenberg, David; Concepcion, Erlinda; Leo, Marenza; Rocchi, Roberto; Marinó, Michele; Keddache, Mehdi; Tomer, Yaron (Frontiers in Endocrinology, 2016)
Graves’ disease (GD) is an autoimmune oligogenic disorder with a strong hereditary component. Several GD-susceptibility genes have been identified and confirmed during the last two decades. However, there are very few studies that evaluated susceptibility genes for GD in specific geographic subsets. Previously, we mapped a new locus on chromosome 3q that was unique to GD families of Italian origin. In the present study we used association analysis of SNPs at the 3q locus in a cohort of GD patients of Italian origin in order to prioritize the best candidates among the known genes in this locus to choose the one(s) best supported by the association. DNA samples were genotyped using the Illumina GoldenGate genotyping assay analyzing 690 single-nucleotide polymorphism (SNPs) in the linked 3q locus covering all 124 LD blocks in this locus. Candidate non human leukocyte antigen (HLA) genes previously reported to be associated with GD and/or other autoimmune diseases were analyzed separately. Three SNPs in the 3q locus showed a nominal association (p<0.05): rs13097181, rs763313, and rs6792646. While these became not significant after Bonferroni correction, we were prioritizing candidate genes at a locus already known to harbor a GD-related gene, not hypothesis testing. Moreover, we found significant associations with the thyroid stimulating hormone receptor (TSHR) gene, the cytotoxic T-lymphocyte antigen-4 (CTLA-4) gene, and the thyroglobulin (TG) gene. In conclusion, we identified 3 SNPs on chromosome 3q that may map a new GD susceptibility gene in this region that is unique to the Italian population. Furthermore, we confirmed that the TSHR, the CTLA-4, and the TG genes are associated with GD in Italians. Our findings highlight the influence of ethnicity and geographic variations on the genetic susceptibility to GD.